Genome wide identification of the Trihelix transcription factors and overexpression of Gh_A05G2067 (GT‐2), a novel gene contributing to increased drought and salt stresses tolerance in cotton - Magwanga, Richard O.; Kirungu, Joy N.; Pu Lu; Xiu Yang; Qi Dong; Xiaoyan Cai; Yanchao Xu; Xingxing Wang; Zhongli Zhou; Yuqing Hou; Regina Nyunja; Agong, Stephen G.; et al. (Wiley Online Library, 2019)
We identified 102, 51 and 51 proteins encoded by the trihelix genes in Gossypium hirsutum, Gossypium arboreum and Gossypium raimondii, respectively. RNA sequence data and real‐time quantitative polymerase chain reaction analysis showed that Gh_A05G2067 (GT‐2) was highly upregulated under drought and salt stress conditions. Transient expression of GT‐2‐green fluorescent protein fusion protein in protoplast showed that GT‐2 was localized in the nucleus. The overexpression of GT‐2 conferred an enhanced drought tolerance to cotton, with lower malondialdehyde, hydrogen peroxide contents and higher reactive oxygen scavenging enzyme activities. Moreover, chlorophyll content, relative leaf water content (RLWC), excised leaf water loss (ELWL) and cell membrane stability (CMS) were relatively stable in the GT‐2‐overexpressed lines compared to wild‐type (WT). Similarly, stress‐responsive genes RD29A, SOS1, ABF4 and CBL1 were highly upregulated in the GT‐2‐overexpressed lines but were significantly downregulated in WT. In addition, the GT‐2‐silenced cotton plants exhibited a high level of oxidation injury, due to high levels of oxidant enzymes, in addition to negative effects on CMS, ELWL, RLWC and chlorophyll content. These results mark the foundation for future exploration of the trihelix genes in cotton, with an aim of developing more resilient, versatile and highly tolerant cotton genotypes.
Abstract